ملمح الاستشراف في قصة جولة في دنيا الخيال لأحمد رضا حوحو مقاربة - سيميائية تأويلية - - عايب, فاطمة الزهراء (جامعة الوادي - University of Eloued, 2023)
يروم المقال تسليط الضوء على قصة جزائرية معنوّنة بجولة في دنيا الخيال، وهي قصة من قصص رضا حوحو المتضمنة من خلال مؤلفاته، وقد كان للقصة كنوزها المتخفية وراء سطورها إذ حاور فيها القاص الكثير من القضايا التي تحتاج التحليل والبحث عن المرامي الخفية المدفونة في أصقاع النص القصصي. ولما كان القاص مفكرا ومبدعا وداعيا مناهضا لترسيخ القيم الإنسانية والوطنية، فقد شكّلت هذه القصة كنزا غنيا بالدلالات التي فيها الكثير من الأبعاد الهامة ،والتي اخترنا منها تناول ملمح الاستشراف إذ سنتناولها بالتحليل وفق مقاربة سيميائية تأويلية متناولين بعض المقاطع السردية بالتحليل واستكشاف البعد الاستشرافي ، وما يحمله من شحنات دلالية للتوعية والعظة باعتبار ما نعايشه حاضرا وعشناه ماضيا يحتاج رؤية استشرافية لتجنبه والتحذير من مخاطره مستقبلا The article aims to shed light on an Algerian story entitled A Tour in the World of Fantasy, which is one of Reda Houhou's stories included through his writings. And since the narrator was a thinker, creator, and advocate against the consolidation of human and national values, this story constituted a rich treasure of connotations that have many important dimensions, from which we chose to deal with the aspect of foresight, as we will deal with it by analysis according to an interpretive semiotic approach, dealing with some narrative passages with analysis and exploring the forward-looking dimension, and what it carries. From indicative shipments to raise awareness and exhortation, considering what we live in the present and lived in the past, which requires a forward-looking vision to avoid it and warn of its dangers in the future.
مقال
Keywords: القصة أحمد رضا ح ; ح ; الاستشراف سيمياء التأ ; يل; the story ; Ahmed ; Reda ; Houhou ; perspective ; semiotics ; of ; nterpretation